Home environmental fungus: the hidden killer - Shrivastava, Bijal M.; Jaiswal, Kunal Kumar; Budhreja, Siddharth; Tiwari, Abhinav (International Journal of Contemporary Pediatrics, 2018)
Hypersensitivity pneumonitis is generally attributed to inhalational organic dust, commonly due to exposure to dust at occupation or hobbies. Hypersensitivity pneumonitis or extrinsic allergic alveolitis is an inflammatory syndrome of lungs resulting from immunologically induced inflammation secondary to various airborne allergens. It is relatively rare in childhood. Knowledge of classical HRCT finding of lungs and use of antigen specific IgG and IgM antibodies (despite the false positive and false negative) analysis can act as supportive evidence for making diagnosis of Hypersensitivity pneumonitis. We report a case of 4 yrs old girl child who despite being symptomatic, remained undiagnosed for 18-24 months, was on bronchodilator therapy suspecting pathophysiology being Hyperreactive airway disease but had recurrent episodes. When her hypoxic condition worsened later on, she was further investigated to rule out other differential, HRCT done was suggestive of childhood interstitial lung disease. The allergens test done for aspergillus species was positive in home environment and in her blood. She responded to steroids therapy and removal of offending agents from home environment. This case shows the importance of home environment in causing life threatening respiratory disease in children. She was diagnosed with Hypersensitivity pneumonitis, rare in childhood.